2020
DOI: 10.3390/ijerph17145169
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced N2O Production Induced by Soil Salinity at a Specific Range

Abstract: Nitrous oxide (N2O) as a by-product of soil nitrogen (N) cylces, its production may be affected by soil salinity which have been proved to have significant negative effect on soil N transformation processes. The response of N2O production across a range of different soil salinities is poorly documented; accordingly, we conducted a laboratory incubation experiment using an array of soils bearing six different salinity levels ranging from 0.25 to 6.17 dS m−1. With ammonium-rich organic fertilizer as their N sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…Soil moisture has a significant effect on N 2 O emissions from saline soil. For instance, 4.7-37.6 and 5.0-15.3 times higher N 2 O emissions at 100% soil moisture level than at 50 and 75% soil moisture levels, respectively, was reported by Li et al [85], and it was mainly due to an increased rate of nitrification with increasing soil moisture [85]. Thapa et al [86] reported that increasing salinity from 0.81 to 4.65 dS m −1 increased N 2 O flux at 90% of Water-filled pore space (WFPS) but reduced at 60% of WFPS in sulfate-dominated saline soil and it was due to that denitrifying bacteria performed more efficiently even at higher salinity levels because water addition reduces the adverse effect of salinity [86].…”
Section: Ghg Emissions Frommentioning
confidence: 65%
See 2 more Smart Citations
“…Soil moisture has a significant effect on N 2 O emissions from saline soil. For instance, 4.7-37.6 and 5.0-15.3 times higher N 2 O emissions at 100% soil moisture level than at 50 and 75% soil moisture levels, respectively, was reported by Li et al [85], and it was mainly due to an increased rate of nitrification with increasing soil moisture [85]. Thapa et al [86] reported that increasing salinity from 0.81 to 4.65 dS m −1 increased N 2 O flux at 90% of Water-filled pore space (WFPS) but reduced at 60% of WFPS in sulfate-dominated saline soil and it was due to that denitrifying bacteria performed more efficiently even at higher salinity levels because water addition reduces the adverse effect of salinity [86].…”
Section: Ghg Emissions Frommentioning
confidence: 65%
“…N 2 O emissions from low salinity wetland soils (0.060 mg kg −1 ) were reported higher as compared to high salinity wetland soils [26]. It is reported that the addition of salts up to a certain threshold may enhance the N 2 O emissions and decrease thereafter [85]. The lower salinity level inhibits both the steps of nitrification (conversion of NH 4…”
Section: Effect Of Salinity/sodicity On Methanogenesis/methanotrophsmentioning
confidence: 97%
See 1 more Smart Citation